Program Asesmen Kompetensi Minimum (AKM) di Sekolah Dasar - Nurwahidah, Ima; Sopyan Iskandar; Tita Mulyati (Elementary Teacher Education Program, Majalengka University, 2023)
The challenge of education is the low quality of education in Indonesia. Basic competency assessment is needed for students to be able to improve self-quality and positive participation. The purpose of this study is to describe the minimum competency assessment program (AKM) in elementary schools. The research method uses literature study methods from various book sources and scientific journals on Google Scholar through the Publish or Perish application. The stages of literature study research through: 1) making research questions, 2) reviewing literature, 3) choosing literature that is appropriate to the topic, 4) analyzing literature content, 5) compiling literature review articles, and 6) publishing literature articles. The results showed that the measurement of the quality of education certainly requires an assessment. AKM is a process to collect information about student learning progress. Based on observations in several schools and literature reviews, teachers have difficulty in following AKM because of their limited understanding of AKM and computer optimization in accessing AKM programs. The AKM program aims to measure the extent of students' literacy and numeracy skills in a school. This AKM program also measures the character and learning environment in a particular school. It can be concluded that in 2022, the results of AKM in several elementary schools based on quality report cards have reached the medium category, meaning that these elementary schools have met the minimum standards.